The Space Shuttle Disaster: Bencana Kapal Angkasa - Md Salleh, Nursafa Ezlinda; Adawiyah, Rabiatul; Zulaffendi, Nur Alya Qistina; Mohd Albe, Nur Izzah Insyirah; Zulkhairi, Syazrina Arisha; Adnan, Nur Izzati; Yahaya, Nur Haziqah; Nur Dini Qistina; Mat Rejab, Siti Hajar Arbain (Applied Information Technology And Computer Science, 2023)
This research investigates the events surrounding the space shuttle Challenger’s ill-fated Mission 51-L on January 28, 1986. Carrying seven individuals, including the notable "Teacher in Space" Christa McAuliffe, the Challenger met a catastrophic end just 75 seconds after liftoff. The study involved issues of risk management, communication management, integration management, human resource management, and quality management. The results indicate how the project manager handle the issues and what caused the explosion. The consequences of the Challenger disaster highlight a perceived lack of direction within NASA, emphasizing the necessity for organizational improvements to enhance safety and prevent future incidents.